PREVALENCE AND ASSOCIATION OF GLYCOSURIA WITH SEVERAL RISK FACTORS FOR DIABETES MELLITUS IN PRIMARY SCHOOL CHILDREN IN BALI - Sutawan, Ida Bagus Ramajaya; Suryawan, I Wayan Bikin; Arimbawa, I Made (Medicina, 2015)
Nowadays, diabetes mellitus (DM) is often found in children. One of important screening for DM isurine examination to determine glycosuria. The current data on the prevalence of glycosuria in childrenin Indonesia, including Bali is very limited.The purpose of this study is to determine the prevalence ofglycosuria in primary school children in Bali and the association of several risk factors for DM on theoccurrence of glycosuria.A cross sectional study of children aged 6-12 years in several primary schoolsin Bali was done. Samples were taken using multistage random sampling technique. Glycosuria wasdetermined by urine reagent stripsand determination of risk factors for DM was by questionnaire andphysical examination. Total of 1020 children were examined in this study. Fiftyone point five percentsof samples were male, obesity was found in 36.8% of samples. Family history of DM was found in 2.6%of samples. This study found 17 cases of glycosuria with a prevalence of 1.7%. Several factors werefound associated with glycosuria, including obese with OR 5.32 (95% CI 1.65 to 17.16; P=0.005), familyhistory of DM with OR 12.98 (95% CI 3.11 to 54.27; P<0.001), and male gender with OR 6.05 (CI 95%1.34 to 27.33; P=0.019).Based on this study, it could be concluded thatthe prevalence of glycosuria wasquite high at primary school children in Bali. Therefore glycosuria screening in children needs to bedone,  especially  in  those with  risk  factors  for DM  to  detect  this  disease  earlier.  [MEDICINA2014;45:156-160].
Keywords: glycosuria, children prevalence